2009
DOI: 10.4103/0970-4388.50817
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of concentration of sucrose, endogenous pH, and alteration in the plaque pH on consumption of commonly used liquid pediatric medicines

Abstract: These sweeteners along with their low endogenic pH form a high cariogenic formulation. Thus, nonsucrose (noncariogenic) or sugar-free medications are needed to be prescribed along with proper oral hygiene care to the children under medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…The HANNA digital pH meter used in our study is more accurate and efficient than conventional electrode pH meter. 12,22 In our study, three out of seven PLM had pH below the critical pH (5.5) of the oral cavity. The range was from 4.22 to 6.10 showing that all were acidic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The HANNA digital pH meter used in our study is more accurate and efficient than conventional electrode pH meter. 12,22 In our study, three out of seven PLM had pH below the critical pH (5.5) of the oral cavity. The range was from 4.22 to 6.10 showing that all were acidic.…”
Section: Discussionmentioning
confidence: 99%
“…In an in vivo study, it was concluded that PLM causes a drop in plaque pH sufficient to cause decalcification within 2 to 10 minutes, following its initial exposure to the teeth. 12 Furthermore, high concentrations of fermentable carbohydrates in PLM may facilitate the growth of Streptococcus mutans by rapidly metabolizing sugars to acids; thus, initiating enamel demineralization. The HANNA digital pH meter used in our study is more accurate and efficient than conventional electrode pH meter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Sunitha et al 14) said inappropriate use of liquid medicines would have enormous potential to induce dental caries as syrups such as antipyretic·analgesic medicines, cough syrup with 10% of sucrose made experimental plaque's pH lower.…”
Section: Introductionmentioning
confidence: 99%